IMPLEMENTASI IPTEK BAGI MASYARAKAT (IbM) PADA PENGRAJIN MINIATUR MENARA - Rina Fiati; Esti Wijayanti (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
This activity of Community Service aims to develop and form an economically independent group of society,to enhance the development of minaret miniature's craftsmen in seizing market opportunities by means ofimproving its product quality and marketing. The specific target expected to reach by the partner-craftsmenis to improve the craft design so as to develop its sales. The method used as a solution to overcome theseproblems is the accompaniment and strengthening of the production process. The problem solving is in itsproduction process, i.e. to produce quality products and e-commerce training for minarets miniature'scraftsmen in Bacin Village, Kudus Regency. The results obtained from the activity are Introduction ofcomputer information technology to craftsmen-partners, Introduction and training of internet and websitemanagement, making e commerce for minaret miniature's craftsmen to market their products on ecommerce basis.